2011
DOI: 10.1016/j.clay.2011.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic acetalization of carbonyl compounds over cation (Ce3+, Fe3+ and Al3+) exchanged montmorillonites and Ce3+-exchanged Y zeolites

Abstract: Under ambient reaction conditions, a one-pot acetalization of carbonyl compounds with methanol was carried out over a series of solid acid catalysts. Ion-exchanged montmorillonite samples were prepared by a metal cation (Ce 3+ , Fe 3+ and Al 3+) exchange from the activated K-10 montmorillonite. These materials have been characterized by wide-angle X-ray scattering (WAXS), solid-state nuclear magnetic resonance spectroscopy (solid-state NMR), temperature programmed desorption of ammonia (NH 3-TPD) and Brunauer-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 75 publications
0
17
0
Order By: Relevance
“…All NMR spectra were acquired on an Avance III 500 (Bruker-Biospin) spectrometer using a single-pulse sequence and operating at a Larmor frequency of 500. 13 [38][39][40][41][42][43][44][45]. It has been demonstrated that a linear correlation between the observed 31 P NMR chemical shifts and the strengths of Brønsted acidity may be inferred [50,51] by means of such 31 P-TMPO NMR approach.…”
Section: Catalyst Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…All NMR spectra were acquired on an Avance III 500 (Bruker-Biospin) spectrometer using a single-pulse sequence and operating at a Larmor frequency of 500. 13 [38][39][40][41][42][43][44][45]. It has been demonstrated that a linear correlation between the observed 31 P NMR chemical shifts and the strengths of Brønsted acidity may be inferred [50,51] by means of such 31 P-TMPO NMR approach.…”
Section: Catalyst Characterizationmentioning
confidence: 99%
“…In addition, acetalization carried out over these acid catalysts also suffered from inherent problems such as highly susceptible to water and excessive amounts of by-products. As such, considerable efforts have been made in developing more durable solid acid catalysts for acetalization of aldehyde with alcohol, for examples, supported Lewis acid [10][11][12], zeolites [13,14], montmorillonites [5,15], and ion exchange resins [16][17][18]. Nonetheless, issues related to product selectivity, environmental safety, spent catalyst disposal, and catalyst recyclability remained as critical challenges for the design and fabrication of highly active catalysts for acetalization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Montmorillonite, is one of the most expandable minerals (Clay 2:1) characterized by its laminar organization, consisting of two tetrahedral layers of silica and a central octahedral layer of aluminum oxide [21,[25][26][27][28]. Both possess a negative charge as a consequence of the isomorphous substitution process, providing a high cation-exchange capacity of ions [23][24][25][26][27][28][29][30]. In addition, the high porosity of clay is widely used in the removal of metallic ions present in aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the high porosity of clay is widely used in the removal of metallic ions present in aqueous solutions. This process occurs following two mechanisms: cation exchange (charge effect) and the formation of inner sphere complexes, due to the ionization of surfaces silanol sites ( Si OH) and aluminols ( Al OH) [18,29,30].…”
Section: Introductionmentioning
confidence: 99%